2014
DOI: 10.1371/journal.pone.0104185
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of Early Life Adversity on Reward Processing in Young Adults: EEG-fMRI Results from a Prospective Study over 25 Years

Abstract: Several lines of evidence have implicated the mesolimbic dopamine reward pathway in altered brain function resulting from exposure to early adversity. The present study examined the impact of early life adversity on different stages of neuronal reward processing later in life and their association with a related behavioral phenotype, i.e. attention deficit/hyperactivity disorder (ADHD). 162 healthy young adults (mean age = 24.4 years; 58% female) from an epidemiological cohort study followed since birth partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
125
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(141 citation statements)
references
References 78 publications
11
125
1
4
Order By: Relevance
“…This may be partially explained by likely inherent differences between accumbal responsiveness to drugs of abuse as employed in animal studies, and to the anticipation of monetary-based reward as is typically utilized in human experiments. However, it should be noted that the studies showing blunted accumbal responses to reward following chronic juvenile stress also found that NAc hypoactivity strongly predicted symptoms of anhedonia and depression (Goff et al, 2013; Boecker et al 2014; Corral-Frias et al, 2015; Hanson et al, 2015). Moreover, anhedonia in participants exposed to repeated juvenile stress was linked to problematic alcohol use arising from the use of substances as a coping mechanism (Corral-Frias et al, 2015).…”
Section: Impact Of Chronic Juvenile Stress On Nucleus Accumbens Anmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be partially explained by likely inherent differences between accumbal responsiveness to drugs of abuse as employed in animal studies, and to the anticipation of monetary-based reward as is typically utilized in human experiments. However, it should be noted that the studies showing blunted accumbal responses to reward following chronic juvenile stress also found that NAc hypoactivity strongly predicted symptoms of anhedonia and depression (Goff et al, 2013; Boecker et al 2014; Corral-Frias et al, 2015; Hanson et al, 2015). Moreover, anhedonia in participants exposed to repeated juvenile stress was linked to problematic alcohol use arising from the use of substances as a coping mechanism (Corral-Frias et al, 2015).…”
Section: Impact Of Chronic Juvenile Stress On Nucleus Accumbens Anmentioning
confidence: 99%
“…In the small number of clinical studies that have examined accumbal function in either human adolescents or adults reporting experiences of repeated social and non-social juvenile stress, hypoactivity of the NAc in response to either reward-related stimuli or reward anticipation is observed (Goff et al, 2013; Boecker et al 2014; Corral-Frias et al, 2015; Hanson et al, 2015, 2016; but see Casement et al, 2014). Initially this would appear to stand in contrast both to the greater incidence of substance abuse disorders seen in victims of childhood stress, and to the increased dopamine activity in the NAc seen in some chronic juvenile stress animal models as discussed above (Table 5).…”
Section: Impact Of Chronic Juvenile Stress On Nucleus Accumbens Anmentioning
confidence: 99%
“…Indeed, early life adversity associated with the development of ADHD impacted differentially on reward processing in adulthood, leading to hyporesponsiveness during reward anticipation and hyperresponsiveness when receiving a reward (Boecker et al, 2014). Externalizing and impulsive but non-psychopathic individuals may thus be characterized by a lower tonic DA activity and a consequent increase in the signal-to-noise ratio of positive prediction-errors, thereby potently boosting behavioral responses to a wide range of environmental stimuli and increasing the risk for impulse-driven disinhibition (Sikström and Söderlund, 2007;Wickens, 2008, 2009).…”
Section: Phasic Mesolimbic Da Reactivity In Psychopathymentioning
confidence: 99%
“…Similarly in humans, adversity experienced in childhood has been associated with elevated levels of dopamine in adulthood (Egerton et al, 2016), and increased ventral striatal dopamine response to amphetamine. In other cases however, there appears to be a blunted sensitivity to rewards as measured by fMRI (Boecker et al, 2014;Dillon et al, 2009;Hanson et al, 2016;Mehta, GoreLangton, Golembo, & Colvert, 2010;Weller & Fisher, 2012), which may be indicative of hypodopaminergic striatal functioning; these contradictory findings may be a result of differences in the timing, type, and severity of adversity experienced.…”
Section: Discussionmentioning
confidence: 99%